Distributive justice - Allingham, Michael (Abingdon, Oxon : Routledge, 2014)
'This book presents a critical appraisal of the main theories of distributive justice, that is, theories that seek to specify what is meant by a just distribution of goods among members of society. It does so in a framework in which all liberal theories of justice are seen as expressions of laissez-faire with compensations for factors that they consider to be morally arbitrary. More specifically, these theories are interpreted as specifying that the outcome of individuals acting independently, without the intervention of any central authority, is just, provided that those who fare ill for reasons that the theories deem to be arbitrary, for example, because they have fewer talents than others, receive compensation from those who fare well. The theories considered may be ordered from those which treat the most factors as being arbitrary to those which treat the least. They are Rawls's justice as fairness, Dworkin's equality of resources, what may loosely be called Steiner-Vallentyne common ownership theories, and Nozick's entitlements theory. The book considers the extent, if any, to which the theories discussed can accommodate both liberty and equality. It concludes that any such accommodation is problematic, but that if it is to be found it will be found among the common ownership theories.'--
Includes bibliographical references and index.
Keywords: Distributive justice